2012
DOI: 10.1007/s12265-012-9396-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of High Content Imaging Methods for Cell Death Detection in Human Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Human pluripotent stem cell-derived cardiomyocytes (hPSC-CM) are being investigated as a new source of cardiac cells for drug safety assessment. We developed a novel scalable high content microscopy-based method for the detection of cell death in hPSC-CM that can serve for future predictive in vitro cardio-toxicological screens. Using rat neonatal ventricular cardiomyocytes (RVNC) or hPSC-CM, assays for nuclear remodelling, mitochondrial status, apoptosis and necrosis were designed using a combination of fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 35 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…For assessment of cardiotoxicity, Mioulane and co-workers [162] triggered cell stress with the cell-permeable protein kinase C inhibitor, chelerythrine. Coupling staining cells with potentiometric dye (TMRM; tetramethylrhodamine methyl ester), caspase-3 or BOBO-1 with Cellomics Arrayscan imaging assessed mitochondrial function, apoptosis and cell death, respectively.…”
Section: Towards Industrial Phenotyping Of Hpsc-cmsmentioning
confidence: 99%
“…For assessment of cardiotoxicity, Mioulane and co-workers [162] triggered cell stress with the cell-permeable protein kinase C inhibitor, chelerythrine. Coupling staining cells with potentiometric dye (TMRM; tetramethylrhodamine methyl ester), caspase-3 or BOBO-1 with Cellomics Arrayscan imaging assessed mitochondrial function, apoptosis and cell death, respectively.…”
Section: Towards Industrial Phenotyping Of Hpsc-cmsmentioning
confidence: 99%
“…In addition to validating the efficacy of drugs such as Ro 31-8220, the hiPSC-CM system will be useful in evaluating potential cardiotoxicity, which is well established issue associated with kinase inhibitors [166]. Thus, Mioulane and co-workers [167] triggered cell stress with the cell-permeable protein kinase C inhibitor, chelerythrine. Combining stains for TMRM (a potentiometric dye; tetramethylrhodamine methyl ester), caspase-3 or BOBO-1 with Cellomics Arrayscan imaging, they assessed mitochondrial function, apoptosis and cell death, respectively and demonstrated that hPSC-CMs are less susceptible to chelerythine-stimulated apoptosis compared to rat neonatal ventricular CMs.…”
Section: Modeling Conduction System Defects (Csds): Dm1 Case Studymentioning
confidence: 99%
“…For example, Sirenko et al (242) have used HCI platforms to perform CalceinAM, Hoechst, and MitoTracker imaging in hiPSC-CMs to evaluate the cardiotoxicity of 131 drugs affecting Na ϩ , K ϩ , and Ca 2ϩ channels, as well as adreno-, dopamine, and histamine receptors. Mioulane et al (193) also used the Thermo Scientific Arrayscan imaging platform to study cellular stress induced by chelerythrine, a cell-permeable protein kinase C inhibitor, by performing combined TMRM, caspase-3, and BOBO-1 staining to measure mitochondrial content, apoptosis, and cell death, respectively. More detailed high content assessment of hiPSC-CM mitochondrial function has been performed by measuring glycolysis and oxidative phosphorylation (OXPHOS) using the Seahorse Extracellular Flux Analyzer (63,289).…”
Section: Generation and Characterization Of Hipsc-cms At A High-thmentioning
confidence: 99%